1999
DOI: 10.1017/s0950268899002046
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental transfer of measles and total IgG

Abstract: This study was conducted to evaluate factors affecting the levels of total IgG (tIgG) and measles specific IgG (mIgG) in mother and cord sera, and the efficiency of transplacental transport of tIgG and mIgG. The study was conducted in four hospitals in Oporto, Portugal, where 1539 women and their newborns were enrolled. Measles IgG levels were lower among vaccinated mothers and respective cord sera than among vaccinated counterparts. Cord mIgG was strongly correlated with maternal levels in both vaccinated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
52
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 23 publications
11
52
4
Order By: Relevance
“…Few studies have measured the placental transfer of specific antibodies to preterm infants. With few exceptions [Linder et al, 1998;Wesumperuma et al, 1999], the specific antibody levels detected in preterm infants were significantly lower than those in term infants [Christensen et al, 1984;Linder et al, 1998;Gonçalves et al, 1999;Ozbek et al, 1999;Costa-Carvalho et al, 1999], as also seen in the present study. Ozbek et al [1999], studying passive immunity against measles at different gestational age intervals, demonstrated a higher transfer ratio than the total CMV IgG ratio found here (82% vs. 57%, respectively) for less than 32 weeks of gestational age, whereas similar ratios were found for gestational ages above 32 weeks (approximately 85%).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Few studies have measured the placental transfer of specific antibodies to preterm infants. With few exceptions [Linder et al, 1998;Wesumperuma et al, 1999], the specific antibody levels detected in preterm infants were significantly lower than those in term infants [Christensen et al, 1984;Linder et al, 1998;Gonçalves et al, 1999;Ozbek et al, 1999;Costa-Carvalho et al, 1999], as also seen in the present study. Ozbek et al [1999], studying passive immunity against measles at different gestational age intervals, demonstrated a higher transfer ratio than the total CMV IgG ratio found here (82% vs. 57%, respectively) for less than 32 weeks of gestational age, whereas similar ratios were found for gestational ages above 32 weeks (approximately 85%).…”
Section: Discussionsupporting
confidence: 87%
“…Various data suggest that the influence of gestational age on the efficiency of antibody transport may vary according to the antigen tested and to the characteristics of the antibody against a given antigen. In this regard, viral antibody concentrations in preterm infants are lower than [Linder et al, 1998;Gonçalves et al, 1999;Ozbek et al, 1999] or similar to [Linder et al, 1997;Wesumperuma et al, 1999] those in term infants.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Since immunity to measles had been acquired through measles vaccinations in women aged <35 years but by natural infection in women aged ≥35 years, these results can be explained by the increased immunity against measles viruses in naturally immune women than in vaccinated women [21,[24][25][26][27]. Leuridan et al [24] found, in the United Kingdom in 2008, that vaccinated women had significantly lower IgG titres than naturally immune women (779 mIU/ml vs. 2, 687 mIU/ml, p<0.001) and that the neonates of vaccinated women also had significantly lower IgG titres than the neonates of naturally immune women (698 mIU/ml vs. 2,221 mIU/ml, p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…This result can be explained by three factors: (1) greater proportion of neonates of vaccinated women in 2013 than in 2003; (2) waning vaccine-induced immunity for measles antibodies; and (3) lower circulation of wild measles viruses after 1980. Several studies have shown that neonates of vaccinated women have lower protective immunity levels against measles than neonates of naturally infected women [21,[24][25][26][27], and that vaccine-induced measles antibodies wane with time [23]. Consequently, the higher proportion of neonates of vaccinated women and the lower proportion of naturally immunised women in 2013 than in 2003 has generated a lower prevalence of neonates protected against measles in 2013 than in 2003.…”
Section: Discussionmentioning
confidence: 99%